Collagen Structure and Mechanics - Fratzl, Peter (Springer US : Imprint: Springer, 2008)
Collagen: Structure and Mechanics provides a cohesive introduction to collagen-rich tissues, such as tendon, bone, cornea or arterials walls. Written in a clear and didactic manner, this volume reviews current knowledge on hierarchical structure, mechanical properties, deformation and strengthening mechanisms, and discusses many applications in biomaterials and tissue engineering. Researchers in the fields of materials, (bio-)engineering, physics, chemistry and biology will gain an understanding of the structure and mechanical behavior of type I collagen and collagen-based tissues in vertebrates, across all length scales from the molecular (nano) to the organ (macro) level. Collagen: Structure and Mechanics is a reference for new researchers entering this area and can serve also as a basis for lecturing in the interdisciplinary field of biological materials science.